Perceived stress and alcohol consumption in adolescents and youths: a scope review - Zamorano-Espero, Jesús Antonio (2023)
Objective: To analyze the available scientific literature on the relationship between perceived stress and alcohol consumption in adolescents and young people. Method: This is a scope review, based on the Arksey and O'Malley methodological framework, using the databases; Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), ScienceDirect and the PubMed and Google Scholar search engines during the months of March and April 2023. Boolean operators were used in the search strategy and different combinations were made. Likewise, inclusion and exclusion criteria were established, in addition, for the selection of potential articles the Joanna Briggs Institute checklist was used. Main results: 11 studies were analyzed, all of them indicate a relationship between the study variables; women are more stressed than men, and stress levels in the general population are low to moderate. Men have higher alcohol consumption compared to women, and in the general population alcohol consumption at some time in life and in the last month prevails, however, there are adolescents and young people with episodes of drunkenness and dangerous alcohol consumption. General conclusion: This study allowed the recognition of perceived stress on alcohol consumption in adolescents and young people. The problem of perceived stress and alcohol consumption is still in progress; Frequently, studies focus on different types of stress, identifying few studies that evaluate perceived stress and alcohol consumption in the population of interest.